(untitled) (International Journal of Engineering and Computer Science, 2017)
Unified Power Flow Controller (UPFC) be one of the most comprehensive FACTS devices which can controls three system parameters independently. In this system a novel configuration of UPFC which consists of a ten switch converter parallel with a series. Capacitor has been proposed to inject desired series voltage. It means that operation of ten-switch converter in this configuration be the same as combination of two converters in conventional UPFC. However, proposed configuration requirements less power electronics switches and gate drive circuits and control scheme becomes simpler than conventional UPFC configuration, using series capacitor parallel by ten switch converter reduce the injection voltage‟s THD, eliminate output filter, also decrease the converters power rating in comparison with conventional UPFC composed of series and shunt converters. The proposed UPFC is modeled using MATLAB/SIMULINK software and simulation results are presented to indicate good operation of the new UPFC.